Minority Discontent as an Internal Destabilization Factor: The Issue of Territorial Minorities in Bosnia and Herzegovina - Savić-Bojanić, Maja (Bałkany Zachodnie w systemie bezpieczeństwa euroatlantyckiego, Bałkany XX/XXI, t. 7, 2015)
This paper comprehensively investigates the current impact of the Dayton imbedded concept of ethnicity which strengthens ethnic belonging and overemphasizes the concept of territorial or constituent minorities in BiH. It argues that statistical differences in the number of constituent peoples across the country significantly contribute to state’s shattered internal stability, overstressing and strengthening the pre-existing nationalistic discourses and creating space for new, but pre-war inspired rhetoric. The analysis is presented through an investigation of the impacts that this issue has on two separate domains of the socio-political life in BiH – the power-sharing and the citizens’ realms.